Thoroughbred Racehorse Hoof Care at ECLIPSE STUD AND STABLE - Henny Endah Anggraeni; Febby Rachmawati; Sutiyarmo Sutiyarmo (Journal of Applied Veterinary Science And Technology, 2022)
Background: Horse hooves have a reasonably heavy function and role, so it is susceptible to abnormalities and diseases. Horse hooves care makes horses more comfortable and protects coffin bone and laminae. Purpose: Explain how thoroughbred horse hooves are proper and correct in Eclipse Stud And Stable to make the horse healthy and grow optimally. Method: Direct observation of horse hooves' treatment, cutting, and paving was conducted by participating in farrier activities in the field and supported by related journal journals as supporting data in completing the information. Results: Horse hooves care every 2-3 days. Hoof care examines hoof condition, hoof cleaning, and horseshoe replacement. Horseshoe replacement once a month. The stage of horseshoe replacement is to open the old horseshoe, hoof cutting, select, and install horseshoes. Conclusions: Horse hooves treatment in eclipse Stud and Stable has been well implemented, as indicated by no problems with horse hooves.